The forming of musical and esthetical interests of teenagers in conditions of studying playing the piano (Pedagogy of Higher and Secondary Education, 2006)
The component structure of musical and esthetical interests of the pupils, pedagogical conditions, methods and ways of the forming musical interests of teenagers, which are studied at music school are discussed m the article.
Keywords: component structure of musical and esthetical interests, pedagogical conditions; methods and ways of their forming